New Straits Times, 07 September 2010 (The New Straits Times Press (M) Bhd, 2010)
Physical exercise can reduce a genetic predisposition to obesity by an average of 40 percent, a new study showed. The research challenges the notion that a inherited propensity to obesity is impossible to overcome and boosts the case for the benefit of more exercise for anyone looking to shed some weight.